Islamic Law on Trading Using Virtual Reality-Based Metaverse - Purwanto , Gatot Hadi; Ajhar , Hakim (Al-Insyiroh: Jurnal Studi Keislaman, 2023)
Islam has given limitations in all human activities in the Qur'an. Islam regulates correct trade procedures such as the fulfillment of legal trade conditions, which include sellers, buyers, goods and agreements. The development of information technology provides major changes to the types and procedures of trade, such as through electronic media (online), or known as the metaverse. Trading in metaverse makes use of a post-reality universe, a continuous and systematic multi-user environment combining physical reality with digital virtuality. Trading in the metaverse requires a medium of interaction between sellers and buyers, one of which is Virtual Reality (VR). Virtual Reality (VR) is a technology allowing users to interact with a computer-simulated environment in the form of an artificial environment or an imaginative environment. In addition to using media for interaction, trading in the metaverse also requires a special currency which can be in the form of crypto coins such as Exie Infinity (AXS), Decentraland (MANA), Sumnium Space (CUBE) obtained from the exchange of real rupiah money into electronic money in the form of crypto coins